Youth increase in developmental assets during a mentoring program regardless of baseline risk - Rzonca, Addie, author; Lucas-Thompson, Rachel, advisor; Zimmerman, Toni, committee member; Merz, Emily, committee member (Colorado State University. Libraries, 2024)
The existing data on the benefits of mentoring programs for adolescent participants are promising, though often unclear in terms of who benefits the most and why (Raposa et al. 2019). In the literature, there tends to be an agreement that risk is likely to moderate program effectiveness to a certain extent, but there is inconsistency about whether greater risk strengthens or weakens program effects (Herrera et al., 2013; Weiler & Taussig, 2017). An important outcome to consider are developmental assets because the negative outcomes of youth risk can be mitigated through the presence of such factors (Scales & Leffert, 1999). The present study seeks to further investigate whether the benefits (in terms of developmental assets) that youth receive from participating in a therapeutic mentoring program differ by their individual level of risk-exposure prior to entering the program. Participants were 676 youth (11-18 years old) who participated in the mentoring program Campus Connections (Haddock et al., 2017) for at least one semester. Each participant was paired with a trained undergraduate mentor and attended four-hour long sessions hosted one night a week for 12 weeks. Each session consisted of four components: one-on-one free time between mentor and mentee, mentor-provided school support, "family style" meals, and prosocial group activities (e.g., games, crafts, team sports). Mentees completed the Developmental Assets Profile (DAP, Search Institute, 2004) before and after completing the program; primary caregivers completed a baseline youth risk assessment. Generalized estimating equation models were used to test the moderating effect of youth risk on change in youth developmental assets (controlling for gender, age, and ethnicity). Time and baseline risk were each significant predictors of developmental assets, such that there were significant increases in assets overall (b = 7.18, se = 1.15, p < .05) and those with higher levels of baseline risk reported lower levels of overall assets (b = -1.51 se = 0.25, p < .05). Whether change varied based on risk was tested via multiplicative interaction between time (baseline vs. post-test) and risk (mean centered) to predict levels of developmental assets. Risk was not a significant moderator, implying that on average youth gain developmental assets in a mentoring program regardless of baseline risk. These findings suggest that mentoring programs can benefit youth with a range of risk exposure.
Keywords: resilience; youth; risk; mentoring